2014
DOI: 10.2174/1874129001408010342
|View full text |Cite
|
Sign up to set email alerts
|

Experiment of Polarization Forces in Scanning Electrostatic Force Microscopy for Measuring Surface Profile of Dielectric

Abstract: For measuring the surface profile of many micro-optical components with complicated shapes, which are made of non-conductive material, the electrostatic force microscopy (EFM) was recommended. The relationship between the polarization force and the tip-to-sample distance was analyzed based on dielectric polarization theory. The prototype of the scanning electrostatic force microscopy was built. The force curves of different samples with different materials and surface shapes were detected by the EFM prototype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…The EFM with dual-height method showed a promising performance in profile measurement of a gold coated diffraction grating. Furthermore, in a subsequent report of our study [5], we confirmed that electrostatic force is observed also from glass sample, indicating the feasibility of applying the dual-height method to insulating materials.…”
Section: Introductionsupporting
confidence: 84%
“…The EFM with dual-height method showed a promising performance in profile measurement of a gold coated diffraction grating. Furthermore, in a subsequent report of our study [5], we confirmed that electrostatic force is observed also from glass sample, indicating the feasibility of applying the dual-height method to insulating materials.…”
Section: Introductionsupporting
confidence: 84%
“…In the initial study, we limited the application of the SEFM to non-insulating (conductive or semiconductive) materials because the system to apply the bias voltage is similar to that of the STM, which can't obtain surface profile of insulating samples. In a subsequent report of our study (He et al, 2014), however it was confirmed that the electrostatic force was observed also on a glass sample which was clamped by an electrode. This indicated a possibility that the SEFM is applicable to insulating materials as well as metal.…”
Section: Introductionsupporting
confidence: 79%
“…Based on the polarization intensity, the density of the polarization charge on the surface of the dielectric medium in the electric field can be calculated, and the electrostatic force between the dielectric medium and the probe is expressed as follows [20]:…”
Section: A Analysis Of Electrostatic Force On the Probementioning
confidence: 99%
“…Further, after the surface of the specimen is coated, the original properties of the specimen being measured are destroyed and cannot be restored. To address this issue, the use of an EFM system to directly measure the surface morphology of the insulating specimen with lager thickness was proposed and a series of early-stage theoretical and experimental studies were conducted; the experimental results indicated that the proposed approach was feasible to some extent [20], [21]. Based on the early-stage preliminary experiments, herein we utilized the established scanning measurement platform to perform partial measurement experiments on different non-conductive materials and different voltage-applying methods and compared the results of these measurements to the true morphology of the specimen.…”
Section: Introductionmentioning
confidence: 99%